Customer-driven manufacturing - Wortmann, J. C. 1950-; Muntslag, D. R. (Dennis R.); Timmermans, P. J. M. (Patrick J. M.) (Chapman & Hall, 1997)
Provides an overview of theory, methods and techniques for the design, redesign and operation of customer order driven manufacturing. The topic is covered using four representative case studies.